PROBLEMATIC ASPECTS OF THE APPLICATION OF THE PRINCIPLE OF EXHAUSTION OF TRADEMARK RIGHTS IN THE EU (EEA) AND OF ITS INTERRELATION WITH CONTRACT LAW: POSSIBLE SOLUTIONS? - Birstonas, Ramunas; Klimkeviciute, Danguole (European Scientific Journal, ESJ, 2014)
The article deals with the issue of exhaustion of trademark rights, which is among the most difficult and controversial questions in the field of intellectual property law. The principle of exhaustion of trademark rights interferes with the scope of trademark owners’ rights as well as the rights of other market participants. Thus, it is important to ensure a fair balance between the interests of both parties, i.e. trademark owners and other market players. Exhaustion of rights being the concept of lex specialis, i.e. trademark law, is closely inter-related with national contract law as well as procedural law of different countries, which makes it difficult to ensure the consistency of case law regarding the application of the principle of exhaustion of trademark rights within different EU (EEA) Member States. The article provides theoretical and practical analysis of some problematic aspects related to the application of the principle of exhaustion of trademark rights, suggesting relevant insights which could serve in trying to find answers in pursuit of more legal certainty and predictability for market participants.